The Role of Cortisol/ACTH Ratio for Screening of Subclinical Hypercortisolism in Patients with Adrenal Incidentalomas - Li, Lele; Yang, Guoqing; Dou, Jingtao; Gu, Weijun; Lv, Zhaohui; Lu, Juming; Mu, Yiming (Experimental and Clinical Endocrinology & Diabetes, 2018)
Introduction The cortisol/ACTH ratio was supposed to be helpful in the screening of subclinical hypercortisolism (SHC) in the published literatures. This study assessed the cortisol/ACTH ratio in patients with adrenal incidentaloma (AI) confirmed to have SHC and investigated its role for screening SCS in patients with AI.Methods This descriptive retrospective study included 183 patients with AIs [45 with SHC and 138 with non-functional adenoma (NFA)]. Cortisol and ACTH levels were measured at 8:00, 16:00, and 0:00, and the cortisol/ACTH ratio was calculated. ROC curve was used to evaluate efficacy of the cortisol/ACTH ratio, explore the best cut-off value and its corresponding sensitivity and specificity.Results The cortisol/ACTH ratios at all time points were significantly higher in the SHC group than the NFA group (P<0.05) and were significantly correlated with serum cortisol levels after the 1-mg dexamethasone suppression test (DST). Area Under the Curve (AUC) of the cortisol/ACTH ratio at 0:00 and midnight serum cortisol levels were 0.893 (0.843–0.943) and 0.831 (0.765–0.806), respectively. A cortisol/ACTH ratio at 0:00 cut-off of 32.18 nM/pM showed a sensitivity of 100% and specificity of 39.1%. The optimal cut-off was 68.83 nM/pM (sensitivity 86.7%, specificity 75.4%).Conclusions Patients with SHC have a higher cortisol/ACTH ratio than those with NFAs. The cortisol/ACTH ratio is significantly correlated with serum cortisol after the 1-mg DST. The diagnostic performance of the cortisol/ACTH ratio at 0:00 is superior to midnight serum cortisol. Therefore, the cortisol/ACTH ratio at 0:00 may be a reliable parameter for SHC screening in patient with AI.